Carte de l'OceÌan Pacifique au Nord de l'Equateur, et des CoÌ‚tes qui le bornent des deux coÌ‚teÌs : |b d'apreÌs les dernieres DeÌcouvertes faites par les Espagnols, les Russes et les Anglois, jusqu'en 1780. - Lotter, Tobias Conrad, 1717-1777 (Tobie Conrad Lotter, 1781)
Map shows settlements and routes of Captains Cook and Clarke along coastlines of northeastern Asia and northwestern North America; route of Spanish galleons between Manilla and Acapulco. Relief shown pictorially. Scale not given.